Coexistence of papillary thyroid microcarcinoma and mucosa-associated lymphoid tissue lymphoma in a context of Hashimoto’s thyroiditis - Levy Blitchtein, Saul (2016)
Papillary thyroid cancer (PTC) represents 80%-85% of thyroid cancer and its prevalence has been rising in the last decades. Primary thyroid lymphoma (PTL) accounts for 3% of extranodal lymphomas and about 5% of thyroid malignancies, having a prevalence of one or two cases per million people. Mucosa-Associated Lymphoid Tissue lymphoma represents approximately 30% of PTL. Both entities have an indolent course and a very good prognosis. Diagnosis is made by ultrasound and fine needle aspiration (FNA) or surgery specimen pathology. They have also been associated with HT, but pathogenesis and its links remains to be known. Treatment remains controversial and surgery is generally accepted in cases of disease limited to thyroid, as the present. Patients with thyroid nodules should be observed and followed. If there is an enlargement by ultrasound or clinical symptoms, FNA should be performed promptly. Patients with Hashimoto’s thyroiditis (HT) deserve additional surveillance, since this condition is associated with both PTC and PTL. In this case, the management with surgery and radioactive iodine ablation therapy was effective for both entities. Patients with thyroid nodules should be properly evaluated with ultrasound and thyroid function tests. If there is an enlargement of the neck, reported by symptoms or ultrasound, it requires further investigation. HT is associated to both PTC and PTL so if the enlargement of the nodules is on this context additional tests such as FNA should be performed. In this case, the patient was managed with surgery and radioactive iodine ablation therapy and it was effective for both entities.